Distributive communicative behaviour in Danish and Spanish negotiation interaction - Grindsted, Annette (HERMES - Journal of Language and Communication in Business, 1989)
This article describes preliminary results of a comparative study of communicative behaviour in Danish and Spanish negotiation interaction. The position is taken that from a socio-psychological point of view negotiation strategies may be accounted for in terms of face needs and feeling and display rules. It is argued that distributive behaviour is prevailing in both cultures, but that the corresponding communicative patterns are completely different.